2017
DOI: 10.21475/poj.10.03.17.pne423
|View full text |Cite
|
Sign up to set email alerts
|

Defatted coagulant seeds of Moringa oleifera and Moringa peregrena mediate alleviation of cadmium toxicity in wheat (Triticum aestivum L.) plant

Abstract: Contaminated soil with toxic heavy metals, particularly cadmium, is an environmental originated challenge from various industrial activities such as effluents and mining and affecting crop growth. Cadmium removal from the soil is a problem, therefore we introduced our approach for reinforcing cadmium tolerance in wheat plant by applying powder (1g/kg soil) of fat-free seeds 'defatted seed or seed-cake' from Moringa oleifera and Moringa peregrena trees before wheat exposure to three levels of soil contamination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The results suggest that Moringa oleifera seeds are a natural coagulant that may treat water containing the unwanted concentration of heavy metals and ensure poultry meat is safe for consumption. Interestingly, Hassanein et al (2017) investigated the remediation of chromium-contaminated soil for agricultural purposes by adding (1 g/Kg) of Moringa oleifera. The results showed that powdered Moringa seeds protected the wheat crop against cadmium toxicity.…”
Section: Abiyu Et Al (mentioning
confidence: 99%
“…The results suggest that Moringa oleifera seeds are a natural coagulant that may treat water containing the unwanted concentration of heavy metals and ensure poultry meat is safe for consumption. Interestingly, Hassanein et al (2017) investigated the remediation of chromium-contaminated soil for agricultural purposes by adding (1 g/Kg) of Moringa oleifera. The results showed that powdered Moringa seeds protected the wheat crop against cadmium toxicity.…”
Section: Abiyu Et Al (mentioning
confidence: 99%
“…Besides synthetic chemicals, there are natural ingredients that can be derived from tropical plants which can be used as coagulants, including moringa seeds (Moringa oleifera). Hassanein et al, (2017) reported that moringa defatted seeds powder had conferred protection against cadmium toxicity in wheat. Upon defatted seeds pre-treatments, Cd accumulation has diminished by 3 and 2-folds in shoots and roots, respectively and wheat growth and physiological parameters have improved spectacularly.…”
Section: Introductionmentioning
confidence: 99%
“…In plants, the application of Moringa oleifera leaf extract improved the antioxidant enzyme system of wheat plants under salt stress, improving their performance signi cantly (Yasmeen et al 2013). In a Cd contaminated environment, not only did Moringa coagulate Cd in the soil and thereby prevent its absorption and accumulation in wheat plants, but it also in uenced the expression of genes associated with alleviation of metal toxicity (Hassanein et al 2016).…”
Section: Introductionmentioning
confidence: 99%